PENDEKATAN EXPRESSIVE WRITING PADA NARAPIDANA WANITA YANG MENGALAMI KECEMASAN MENJELANG MASA BEBAS - Ariny Oktaviany; Magdalena S. Halim (MANASA, 2014)
Anxiety is usually experienced by female inmates during their freedom. Itmay be caused due to negative stigma from the society, rejection from theirfamilies and negative perception towards inmates. The anxiety experienced byfemale inmates will show its impact when they return to the society, includingpsychological impact, such as low self-esteem. Therefore it requires sometreatments to minimize their anxiety, such as by expressive writing. The objective of this research is to acknowledge the impact of Expressive Writing approach towards anxiety on female inmates who are waiting for their freedom. The design of this research is mixed method. Participants of the research are 19 female inmates around 21 – 40 years old in average, high school graduates, and most of the participants are already married. The participants are from LPW Palembang and RUTAN Prabumulih. Intervention is performed in six sessions, each session is 15 minutes. Data analysis is using Wilcoxon signed rank test for quantitative approach. The research showed significant difference of anxiety levels after the Expressive Writing sessions. Expressive writing approach is one of some other intervention that can help decreasing the inmates anxiety level. Most of the participants see Expressive Writing as a way to express their emotion which is capable to give relieving effect after performing it. Further research by using this approach is still required therefore the benefit can be seen in various areas.